2014
DOI: 10.1007/s13762-014-0524-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of agar-stabilized nanoscale zero-valent iron particles and removal study of hexavalent chromium

Abstract: In this study, agar-stabilized nanoscale zerovalent iron (A-nZVI) was synthesized using a rheological phase reaction method. The structure and morphology of A-nZVI particles were investigated by X-ray powder diffraction, scanning electron microscopy, transmission electron microscopy and Fourier-transform infrared spectrometry. Batch removal experiments showed that the pH value of solution, hexavalent chromium [Cr(VI)]/A-nZVI mass ratio and reaction time have significant effects on the removal of Cr(VI). A 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…The peaks at 1159.26 and 1010.42 cm −1 were assigned to C-O and C-C stretching vibration of C-O-H bending. This observation is similar to that obtained by Jiao et al [27]. So we conclude the surface of fresh nanoparticle is cover by the starch molecules.…”
Section: Characterization Of Metal Nanoparticlesupporting
confidence: 92%
See 1 more Smart Citation
“…The peaks at 1159.26 and 1010.42 cm −1 were assigned to C-O and C-C stretching vibration of C-O-H bending. This observation is similar to that obtained by Jiao et al [27]. So we conclude the surface of fresh nanoparticle is cover by the starch molecules.…”
Section: Characterization Of Metal Nanoparticlesupporting
confidence: 92%
“…This observation is similar to that obtained by Jiao et al . . So we conclude the surface of fresh nanoparticle is cover by the starch molecules.…”
Section: Resultsmentioning
confidence: 54%
“…These compounds are in accordance with the chemical composition of Table 1 . The characteristic (110) diffraction peak of iron at a 2-theta value was 44.8°, indicating the presence of zero-valent Fe in B-nZVI and GO-B-nZVI [ 24 ]. The phenomenon indicates that zero-valent iron was prepared successfully in the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The investigation revealed that the removal of As(III) required high degree of surface reactivity to ensure the suitable As(III) adsorption capacity and a sufficient contact between adsorbents-As(III). Nanoscale zero valent iron (NZVI), which contains high surface and high surface heterogeneity, has been reported as a promising adsorbent for capturing As(III)/As(V) from contaminated water [10,11].…”
Section: Introductionmentioning
confidence: 99%